Theorem: The sum of the first n positive natural numbers is n(n+1)/2.
Proof: By induction; Let P(n) be the sum of te=he first n positive natural numbers is n(n+1)/2.
- For our base case, we need to show P(0) is true. So, P(0) = 0; which is true.
- For the inductive step, assume that for some n E N that P(n) holds, meaning that 1 +2 + ... + n = n(n+1)/2.
- We assume that P(n) is true, and simplify and replace. So, sum of n+1 = n(n+1)/2 + (n+1).
- n(n+1)/2 + (n+1) = (n+1)(n+2)/2 = P(n+1).
Theorem: Summation of 2i from 0 to n-1 = 2n -1.
Proof: By induction. Let P(n) be summation of 2i from 0 to n-1 = 2n -1.
- base case: P(0) = 0, which is true.
- inductive step: P(n+1) - peel off the last term. You get 2n - 1 + 2n = 2n+1 -1. Which is P(n+1)!